Some simplest integral equalities equivalent to the Riemann hypothesis
UDC 511.3 We show that the following integral equalities are equivalent to the Riemann hypothesis for any real a>0 and any real 0<ε<1, ε eq 1:gather*_-∞^∞(ζ(12+it))a+it\